Strategi Pengembangan Usaha Peternakan Sapi Potong pada BUMDes Siem Kecamatan Darussalam Kabupaten Aceh Besar - Masyitah, Masyitah; Mulyanti, Mulyanti; Muzakir, Muzakir; Salima, Reza; Nurkhatijah, Nurkhatijah; Anwar, Chairil; Agustina, Sri; Mirnawati, Mirnawati (Institut Ilmu Sosial dan Manajemen Stiami, 2024)
BUMDes is a village business institution in the economic sector that is wholly or partially owned by the village and managed by the community and Village Government in an effort to strengthen the village economy and the welfare of the village community that is formed based on the needs and potential of the village. Beef cattle unit as a business unit a Village-Owned Enterprise (BUMDes) in Siem village, Aceh Besar capital. This service aims to develop a series of alternatives for developing a BUMDes cattle business unit in Siem Village, the capital of Aceh Besar. The community service activities was carried on 27 February 2023 in Siem Village, Darussalam Regency, Aceh Besar. The technique of data were collection was done interviews and observation in location. The result community service of this study show that four alternative strategy were beef cattel unit : 1) Improvement of human resources, 2) Availability of food, 3) Increasing the capacity of capital, and 4) Production equipment. The village government requires collaboration from various stakeholders. The village government requires collaboration from various stakeholders. This is necessary to encourage in animal husbandry and empower beef cattle farmers to make their business viable and increase their income. Strategy of provision of forage land and application of appropriate technology in fodder processing.is the priorities strategy in order to improve the growth of cattle industry.